Influencing Factors of the Leadership Model of Women Leaders in Small and Medium-sized Enterprises - Chen , Lihuang; Thianthai, Chuta; Khantanapha, Napaporn (วารสารนวัตกรรมการศึกษาและการวิจัย, 2024)
This research aims to 1) study current situation of female entrepreneurs' leadership in China, 2)To analyst the factors of foundation of the female leadership, practical consciousness, and competitive awareness direct effect female leadership model, 3) analyst mediating role practical consciousness and competitive awareness play a mediating role impact between foundation of the female leadership and female leadership model. This research was quantitative, collected data from female leadership over all China sample of 440 respondents. They were selected by simple random sampling, the instrument for collecting data was a questionnaire with a content validity (IOC) of .941 and a reliability value of Cronbach’s alpha coefficient of .825. Analysis of data via SEM by AMOS. Research found that 1) the majority of respondent 268 women entrepreneurs were born in Chinese Mainland of 64.42%, and 106 women entrepreneurs from Hong Kong and Macao SAR of 35.57%; and 42 women entrepreneurs from Taiwan Province, of 10.09%, their age between 30 to 50 years old is 184, respondents of 68.65%. 2) the direct effect were: foundation of the female leadership direct effect female leadership model, practical consciousness and competitive awareness. For the practical consciousness and competitive awareness direct effect female leadership model. 3) the mediating effect of practical consciousness and competitive awareness play a mediating impact foundation of the female leadership and female leadership model.